Chapter 11 Antagonisms and solidarities in housing movements in Bucharest and Budapest - Florea, Ioana (Taylor & Francis, 2020)
This chapter investigates housing contention in Bucharest and Budapest in the period after the 2008 financial crisis. Our focus of attention is on the antagonisms and solidarities produced across different social positions within current mobilizations around housing. To account for the complexity of housing contention that we observe, we draw on the 'field of contention' notion, focusing specifically on how structural processes shape actors' positions and mutual relations in present social struggles over housing. The main argument is that structural aspects of housing relations are relevant in understanding the alliances, solidarities, antagonisms and conflicts in the field of housing contention, and the various ideologies and political values involved in those dynamics.